2016
DOI: 10.1002/joec.12028
|View full text |Cite
|
Sign up to set email alerts
|

The Need for Dynamic Models of Career Development for Transitioning Offenders

Abstract: Within correctional settings, career development interventions focus on teaching employment skills to offenders to help them obtain work in the community. However, ongoing changes in labor market trends affect job insecurity and, thus, criminal recidivism. This article first reviews some of the existing career development interventions used with offender populations. The authors then suggest that a more dynamic approach to career development—with offenders embracing the paradoxical complexities of making caree… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…Research has found that individuals who have been incarcerated also often exhibit underdeveloped career identities due to gaps in employment and work experiences, which impacts vocational identity development and the ability to adjust in the labor market (Bennett & Amundson, 2016; Meyer & Shippen, 2016). This would suggest that for individuals returning from incarceration, it would be important to strengthen vocational identity which can, in turn, inform and increase the individual's overall career decision‐making self‐efficacy.…”
Section: Introductionmentioning
confidence: 99%
“…Research has found that individuals who have been incarcerated also often exhibit underdeveloped career identities due to gaps in employment and work experiences, which impacts vocational identity development and the ability to adjust in the labor market (Bennett & Amundson, 2016; Meyer & Shippen, 2016). This would suggest that for individuals returning from incarceration, it would be important to strengthen vocational identity which can, in turn, inform and increase the individual's overall career decision‐making self‐efficacy.…”
Section: Introductionmentioning
confidence: 99%
“…This implies that next to the specialized knowledge and skills, generic skills are also essential for successful and innovative application of disciplinary knowledge in the workplace (Jackson and Chapman, 2012;Jackson, 2014a). As a result, these skills are recognized by experts as important factors for individuals' employability (Bennett & Amundson, 2016;Bennett, Dunne, & Carré, 1999;Bridgstock, 2009;Hillage & Pollard, 1998;Knight & Yorke, 2002;McQuaid & Lindsay, 2005;Stiwne & Jungert, 2010), especially for the "ready to work" graduates (Jackson and Chapman, 2012;Kamaliah et al, 2018). The generic skills enable individuals to participate in the labour market as part of a flexible and adaptable workforce (Bennett, 2002;Pitan, 2017).…”
Section: Introductionmentioning
confidence: 99%